Wnt5A Signaling Promotes Defense Against Bacterial Pathogens by Activating a Host Autophagy Circuit - Jati, Suborno; Kundu, Suman; Chakraborty, Arijit; Mahata, Sushil Kumar; Nizet, Victor; Sen, Malini (Frontiers in Immunology, 2018)
Bacterial pathogens are associated with severe infections (e.g. sepsis) and exacerbation of debilitating conditions such as chronic obstructive pulmonary disease (COPD). The interactions of bacterial pathogens with macrophages, a key component of innate immunity and host defense, are not clearly understood and continue to be intensively studied. Having previously demonstrated a role of Wnt5A signaling in phagocytosis, we proceeded to decipher the connection of Wnt5A signaling with infection by pathogenic bacteria, namely Pseudomonas aeruginosa and Streptococcus pneumoniae, which are related with the progression of COPD and sepsis. We found that during the initial hours of infection with P. aeruginosa and S. pneumoniae there is decrease in the steady state levels of the Wnt5A protein in macrophages. Suppression of Wnt5A signaling, moreover, impairs macrophage clearance of the bacterial infection both in vitro and in vivo. Activation of Wnt5A signaling, on the other hand, enhances clearance of the infection. Macrophage mediated containment of bacterial infection in our study is dependant on Wnt5A induced Rac1/Dishevelled activation and cytochalasin D inhibitable actin assembly, which is associated with ULK1 kinase activity and LC3BII accumulation. Our experimental findings are consistent with Wnt5A signaling dependent induction of autophagic killing (xenophagy) of P. aeruginosa and S. pneumoniae, as further substantiated by transmission electron microscopy. Overall, our study unveils the prevalence of a Wnt5A – Rac1 – Dishevelled mediated actin-associated autophagy circuit as an important component of innate immunity in host macrophages that may turn out crucial for restricting infection by leading bacterial pathogens.